Functional health status in children and adolescents after Fontan: comparison of generic and disease-specific assessments. (10th June 2013) - McCrindle, Brian W.; Zak, Victor; Pemberton, Victoria L.; Lambert, Linda M.; Vetter, Victoria L.; Lai, Wyman W.; Uzark, Karen; Margossian, Renee; Atz, Andrew M.; Cook, Amanda; Newburger, Jane W.
Abstract Purpose: The aim of this study was to compare associations between generic versus disease-specific functional health status assessments and patient and clinical characteristics for patients with severe congenital heart disease. Methods: This was a cross-sectional observational study involving 325 single ventricle patients, aged 10–18 years, after Fontan procedure. Enrolled patients underwent a medical history review, laboratory testing, and assessment of the functional health status by completion of the generic Child Report Child Health Questionnaire and the disease-specific Congenital Heart Adolescent and Teenage questionnaire. Correlated conceptually equivalent domains from both questionnaires were identified and their associations with patient and clinical variables were compared. Results: From the generic assessment, patients perceived marginally lower physical functioning (p = 0.05) but greater freedom from bodily pain compared with a normal population (p < 0.001). The equivalent physical functioning/limitations domain of the generic instrument, compared with the disease-specific instrument, had similar associations (higher multi-variable model R2) with medical history variables (R2 = 0.14 versus R2 = 0.12, respectively) and stronger associations with exercise testing variables (R2 = 0.22 versus R2 = 0.06). Similarly, the corresponding freedom from bodily pain/symptoms domains from both questionnaires showed a greater association for the generic instrument with medical history variables (R2 = 0.15 versus R2 = 0.09, respectively) and non-cardiac conditions (R2 = 0.13 versus R2 = 0.06). The associations of each questionnaire with echocardiographic results, cardiac magnetic resonance imaging results, and serum brain natriuretic peptide levels were uniformly weak (R2 range <0.01 to 0.04). Conclusions: Assessment of the physical functional health status using generic and disease-specific instruments yields few differences with regard to associations between conceptually similar domains and patient and clinical characteristics for adolescents after Fontan procedure.